MICROSTRIP ANTENNA FOR RURAL AREA COMMUNICATION PLATFORM - Fikri, Ryan
In this research, design, simulation, realization and implementation of patch antenna for rural area communication platforms. There are two types of antennas used, single patch antenna with a frequency of 2,4 GHz for communication from platform to user and array patch antenna with a frequency of 5,18 GHz to connect between communication platforms. In designing a single 2,4 GHz patch antenna, proximity coupling is used and multiple slots are added to the patch which aims to widen the bandwidth. There are two types of array antennas that will be used, array antenna using proximity coupling and array antenna using inset-fed with Dolph Tscebyscheff power distribution. The antenna uses the FR-4 Epoxy dielectric with relative permittivity (????????) of 4,2, relative permeability (????????) = 1, copper thickness (t) = 0,035 mm and substrate thickness (h) = 1,6 mm and then connected using a 50? SMA connector. Bandwidth based on the antenna simulation results for a single 2,4 GHz patch antenna is 114 MHz where the use of slots on the antenna patch provides additional bandwidth of 21,8 MHz or 23,64%. Patch array antenna 1×4 proximity coupling results gain 8,8 dBi with a horizontal beamwidth 25,8°, while the patch array antenna inset-fed 1×5 Dolph Tschebyscheff power distribution results gain 5,5 dBi and beamwidth horizontal 29,1°. The antenna used on the communication platform are single patch antenna with slots using a 2,4 GHz proximity coupling and patch array antenna 1 × 4 proximity coupling 5,18 GHz. Simulation and measurement results are compared to perceive the overall system performance of the antenna carried.